MIRERC 058/2025: ANALYSIS OF TRENDS IN OVARIAN, ENDOMETRIAL, AND CERVICAL CANCERS IN NAKURU COUNTY, KENYA. - Wanjiru Kamau, Ann; Dr. Frank G. Onyambu, PhD; Dr. Patrick Kubai, (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Ovarian, endometrial and cervical cancers are the most common gynecological cancers that continue to undermine the quality of life of women globally, regionally and in Kenya. The disease burden of gynecological cancers is concerning, with trends in morbidity and mortality predicted to increase over the years. This study aims to analyze the trends in ovarian, endometrial and cervical cancers in Nakuru County. A cross-sectional retrospective study design will be used to abstract health records from the Nakuru Regional Cancer Centre in the period May 2018 to December 2024. The data will be collected using a standard data collection tool prepared using Kobo Collect and analysis done using R Studio. The research findings are expected to describe the annual incidence and prevalence of ovarian, endometrial and cervical cancer from 2018 to 2024, the geographical distribution, the prevalence of comorbidities, and prediction of the statistically significant factors influencing survivorship of patients with ovarian, endometrial and cervical cancer in Nakuru county. The research findings will be useful in accurately quantifying the morbidity and mortality of the selected gynecological cancers in Nakuru county, which will play a critical role in informing evidence-based and data-driven decision-making towards public health prevention and control interventions